The E280A Presenilin-1 Alzheimer mutation produces increased Aß42 depossition and severe cerebellar pathology (1996)
ABSTRACT: Missense mutations in the presenilin 1 (PS1) gene cause the most common form of dominant early–onset familial Alzheimer's disease (FAD)1,2 and are associated with increased levels of amyloid β–peptides (Aβ) ending at residue 42 (Aβ42) in plasma and skin fibroblast media of gene carriers3. Aβ42 aggregates readily and appears to provide a nidus for the subsequent aggregation of Aβ40 (ref. 4), resulting in the formation of innumerable neuritic plaques. To obtain in vivo information about how PS1 mutations cause AD pathology at such early ages, we characterized the neuropathological phenotype of four PS1–FAD patients from a large Colombian kindred5 bearing the codon 280 Glu to Ala substitution (Glu280Ala) PS1 mutation2. Using antibodies specific to the alternative carboxy–termini of Aβ, we detected massive deposition of Aβ42, the earliest and predominant form of plaque Aβ to occur in AD (ref. 6–8), in many brain regions. Computer–assisted quantification revealed a significant increase in Aβ42, but not Aβ40, burden in the brains from 4 PS1–FAD patients compared with those from 12 sporadic AD patients. Severe cerebellar pathology included numerous Aβ42–reactive plaques, many bearing dystrophic neurites and reactive glia. Our results in brain tissue are consistent with recent biochemical evidence of increased Aβ42 levels in PS1–FAD patients and strongly suggest that mutant PS1 proteins alter the proteolytic processing of the β–amyloid precursor protein at the C–terminus of Aβ to favor deposition of Aβ42